Struggling Authorial Identity of Second Language University Academic Writers in Mexico - Troy Crawford; Irasema Mora Pablo; M. Martha Lengeling (Universidad Nacional de Colombia, 2016)
This paper explores the different factors that appear to affect the on-going construction of second language authorial identity in a professional academic environment in Mexico. Through narrative research methodology from a qualitative paradigm, the everyday struggles of two university professors to maintain their professional status in second language writing are explored. The areas of study for these two are chemistry and penal law. With data the learning processes of entering into a community of second language writers are studied as well as the problems they faced and how they resolved them. Finally, the process of negotiating an authorial identity in a second language seems to be a constant underlying struggle composed of a variety of psychological factors.